Review of Year 2004 Sumatra-Andaman Earthquake Tsunami Fault Parameters - Naim, N. N. N.; Mardi, N. H.; Malek, M. A. (International Journal of Engineering and Technology, 2018)
This paper reviews the fault parameters used in the literatures of tsunami source simulations for the 26 December, 2004 Sumatra–Andaman tsunami, as well as understanding of the geology and geography of the Sunda Trench. Although the source of tsunami generation is exclusive, the parameters used in the simulations differ according to source of data, method of parameter derivation and modeling experiences. Hence, identification of possible future source generations and results for best fit parameters obtained from literature review are integrated to be used for future simulations. Based on the literature review conducted, it is clear that the parameters of tsunami source generation play a vital component and indication in amplifying effects in the coastal areas. Hence, earlier identification of possible fault rupture parameters in the Andaman Sea provides an information about the effects of the future risks of tsunami towards the west-coast of Malaysia.